Synthesis of new 3,5-substiuted isoxazole derivatives possessing potential anti-aggregative activity - O. V. Demina; A. V. Laptev; A. U. Lukin; N. E. Belikov; K. V. Zvezdin; M. A. Fomin; A. A. Khodonov; S. D. Varfolomeev; V. I. Shvets (Тонкие химические технологии)
Two new compounds belonging to 3,5-substituted isoxazoles class were synthesized for the action mechanism investigation and the pharmacophore fragment determination of potential anti-aggregative compounds of this class. An attempt to prepare of 5-phenyl-3-(3-pyridyl)isoxazole by the phase-transfer method was described.